OPINI PUBLIK SEBAGAI BAROMETER PEMBENTUKAN CITRA ORGANISASI / PERUSAHAAN - Melita, Yerah (Jurnal Insani, 2016)
Each organization /company in principle have the same goal, namely that the public /society has an assessment, attitude and opinion enjoyable and profitable for the organization /company. In other words, the purpose of the organization/company is to obtain the reputation, credibility and a positive image of the public.To obtain these objectives, the organization/ company must be sensitive and care about the opinions exist and thrive in the community about the organization/company. By knowing and understanding the opinions exist and thrive in the community, organization/company can actualize the aspirations, needs, and expectations of the public.